Design and Analysis of Bogie and Coach of Mass Rapid Transit (Metro) for Nepal - Karki, Parash Jung; Sharrf, Bikash; Tuladhar, Daniel; Mahat, Chiranjeevi (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Mass Rapid Transit (Metro) has become the ultimate solution for city transportation due to its various advantages including traffic issues solv- ing ability, emission free mode, comfortability, speed and efficiency. In developing countries like Nepal where people are deprived of proper transportation system, Metro railway can bring about lots of positive socio-economic changes. A lot of analysis regarding the technical aspects and designing process adapted throughout the globe has been done and the best suited design for the context of Nepal has been included in the paper. A Bogie is a chassis or framework carrying wheels attached to the train, serving as a modular subassembly of wheels and axles. Old bogies are cast models which are huge and bulky in its nature. In order to overcome the limitations of the existing FIAT bogie, a new bogie namely Y32 Bogie is designed to equip with the coach. The coach with the longitudinal arrangements of seats is designed to accommodate the higher number of passengers. The design of the various bogie components is done following the procedures of machine design and various standards that suits the best for our context. The 3D-modeling of the bogie and the coach is performed in CREO PARAMETRIC 5.0. The design of bogie frame is then imported to ANSYS 19.2 for Finite Element Analysis. The analysis on stresses and maximum deformation induced in the bogie frame structure for different materials is performed and the comparison is made to find the best suited design. To achieve the Finite Element Analysis, the load criteria are considered from Indian Railway Standards.